KARAKTER SISWA KELAS VIII SMIP 1946 BANJARMASIN PADA MATA PELAJARAN IPS TERPADU TAHUN AJARAN 2012/2013 - Angriani, Parida; Hastuti, Karunia Puji; Sari, Ratna Kumala (Vidya Karya Jurnal Kependidikan, 2014)
This research aims to determine the character of eight grade students of SMIP 1946 in integrated Social sciences. The type of the data is primary data such as questionnaire result and secondary data such as documentation result and literature associated with the research. The population is all eight grade students of SMIP 1946. Banjarmasin consisting of 98 students. The research showed that 81 of students (81,9%) implement attitude reflecting religious character, 74 of students (75,5%) apply the attitude of respect and attention, 84 of students (85,5%) already have discipline on current regulation in school, 69% of students (70,2%) have implemented diligent attitude in learning, 70 of students (71,2%) had good coscientious attitude about work and taking a decision in learning, and 70 of students (71,7%) have a responsible attitude. Although, there is still little bit of students character that is not corresponds with the expectation. Therefore,Â  it is necessary teacher s role which is more leverage in terms of fostering students attitudes and behaviors .